Investment Decisions and Firm Value: The Moderating Role of Profitability - Melina, Ester; Endri, Endri (International Journal of Economics and Financial Issues, 2024)
Firm value (FV) describes the performance of management in carrying out the work entrusted to them by shareholders related to company management. Shareholders expect Increasing FV because it can achieve the company's goal of maximizing its welfare. The study investigates the influence of investment decision factors and asset turnover (TATO) and the role of Profitability (ROA) as a moderator variable on FV. The research sample includes 32 property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) for 2018-2022. The estimation method applied is a panel data regression model that includes common, random, and fixed effects to test the research hypothesis. Fixed effect model (FEM) estimation based on selected diagnostic tests to test the research hypothesis. Investment decisions proxied by the price-earnings ratio (PER) in the model with ROA moderator, directly without interaction, have a negative impact on FV. Still, the interaction between PER and ROA has a positive but insignificant effect. Conversely, PER does not affect FV without the role of the ROA moderator. TATO, which measures efficiency, positively impacts FV in both models without and with the role of the ROA moderator. On the other hand, TATO has a negative impact on FV if it interacts with ROA. ROA directly without interaction is negatively related to FV. ROA, which acts as a moderator variable, can only moderate TATO negatively on FV.